Diversity and convergences in the evolution of feeding adaptations in ankylosaurs (Dinosauria: Ornithischia)*. (19th May 2017) - Ősi, Attila; Prondvai, Edina; Mallon, Jordan; Bodor, Emese Réka
Abstract: Ankylosaurian dinosaurs were low-browsing quadrupeds that were traditionally thought of as simple orthal pulpers exhibiting minimal tooth occlusion during feeding, as in many extant lizards. Recent studies, however, have demonstrated that effective chewing with tooth occlusion and palinal jaw movement was present in some members of this group. Qualitative and quantitative analysis of feeding characters (i.e. craniodental features, tooth wear patterns, origin and insertion of jaw adductors) reveal at least three different jaw mechanisms during the evolution of Ankylosauria. Whereas, in basal members, food processing was restricted to simple orthal pulping, in late Early and Late Cretaceous North American and European forms a precise tooth occlusion evolved convergently in many lineages (including nodosaurids and ankylosaurids) complemented by palinal power stroke. In contrast, Asian forms retained the primitive mode of feeding without any biphasal chewing, a phenomenon that might relate to the different types of vegetation consumed by these low-level feeders in different habitats on different landmasses. Further, a progressive widening of the muzzle is demonstrated both in Late Cretaceous North American and Asian ankylosaurs, and the width and general shape of the muzzle probably correlates with foraging time and food type, as in herbivorous mammals.